Las raíces de la felicidad, según la mística dominicana (el Maestro Eckhart y Enrique Suso) (2016)
The “Rhineland mysticism” –name frequently used in Francophone circles- or “German mysticism”, should more appropriately be called “Dominican mysticism”; since it is the school of thinking and spirituality that emerged and developed in the Dominican province of Teutonia, in the fourteenth century (religious province that extended through Teutonia, with an extent much larger than todays’ Germany), and whose main representatives are Meister Eckhart, Henry Suso or Seuse and Johannes Tauler, all of them Dominican friars